Assessing the extinction risk of insular, understudied marine species. Issue 2 (12th November 2021) - Thomas, Elin A.; Böhm, Monika; Pollock, Caroline; Chen, Chong; Seddon, Mary; Sigwart, Julia D.
Abstract: Hydrothermal vents are rare deep‐sea oases that house faunal assemblages with a similar density of life as coral reefs. Only approximately 600 of these hotspots are known worldwide, most only one‐third of a football field in size. With advancing development of the deep‐sea mining industry, there is an urgent need to protect these unique, insular ecosystems and their specialist endemic faunas. We applied the IUCN (International Union for the Conservation of Nature) Red List criteria to assess the extinction risk of vent‐endemic molluscs with varying exposure to potential deep‐sea mining. We assessed 31 species from three key areas under different regulatory frameworks in the Indian, West Pacific, and Southern Oceans. Three vent mollusc species were also examined as case studies of different threat contexts (protected or not from potential mining) to explore the interaction of local regulatory frameworks and IUCN Red List category assignment. We found that these assessments were robust even when there was some uncertainty in the total range of individual species, allowing assessment of species that have only recently been named and described. For vent‐endemic species, regulatory changes to area‐based management can have a greater impact on IUCN Red List assessment outcomes than incorporating additional data about species distributions. Our approach revealed the most useful IUCN Red List criteria for vent‐endemic species: criteria B and D2. This approach, combining regulatory framework and distribution, has the potential to rapidly gauge assessment outcomes for species in insular systems worldwide. Abstract : Article impact statement IUCN Red List assessments robustly compare extinction risk from deep‐sea mining at understudied hydrothermal vent habitats. Abstract : Evaluación del Riesgo de Extinción de Especies Marinas Insulares Poco Estudiadas Resumen: Los respiraderos hidrotermales son oasis poco comunes en las profundidades del mar en donde se encuentran conjuntos de fauna con una densidad similar a la de los arrecifes de coral. A nivel mundial, sólo se conocen aproximadamente 600 de estos puntos calientes, la mayoría solamente del tamaño de un tercio de una cancha de fútbol. Conforme avanza el desarrollo de la industria minera en mares profundos, también hay una urgente necesidad por proteger estos ecosistemas únicos e insulares y a su fauna endémica especialista. Aplicamos el criterio de la Lista Roja de la UICN (Unión Internacional para la Conservación de la Naturaleza) para evaluar el riesgo de extinción que tienen los moluscos endémicos de los respiraderos ante una exposición variable a la potencial minería de mar profundo. Evaluamos 31 especies de tres áreas importantes bajo diferentes marcos regulatorios en los océanos Índico, Pacífico Occidental y del Sur. Analizamos tres especies de moluscos de los respiraderos como estudios de caso para diferentes contextos de amenazas (protegidas o no de la minería potencial) para explorar la interacción de los marcos regulatorios locales y la clasificación categórica dentro de la Lista Roja de la UICN. Descubrimos que estos análisis eran sólidos incluso cuando existía algo de incertidumbre en cuanto a la extensión total de la especie individual, lo que permite la valoración de especies que han sido descritas y nombradas recientemente. Para las especies endémicas de las chimeneas, los cambios regulatorios a un manejo basado en el área pueden tener un mayor impacto sobre los resultados de evaluación de la Lista Roja de la UICN que la incorporación de datos adicionales sobre la distribución de las especies. Nuestra estrategia reveló los criterios más útiles de la Lista Roja de la UICN para las especies endémicas de las chimeneas: los criterios B y D2. Esta estrategia, que combina un marco regulatorio con la distribución, tiene el potencial para medir rápidamente los resultados de las evaluaciones para las especies que se encuentran en sistemas insulares en todo el mundo.